Initial Mass Functions of Young Stellar Clusters from the Gemini Spectroscopic Survey of Nearby Galaxies. I. Young Massive Clusters in the Antennae Galaxies - Jae-Rim Koo; Hyun-Jeong Kim; Beomdu Lim (The Astronomical Journal)
The stellar initial mass function (IMF) is a key parameter to understand the star formation process and the integrated properties of stellar populations in remote galaxies. We present a spectroscopic study of young massive clusters (YMCs) in the starburst galaxies NGC 4038/9. The integrated spectra of seven YMCs obtained with GMOS-S attached to the 8.1 m Gemini South telescope reveal the spectral features associated with stellar ages and the underlying IMFs. We constrain the ages of the YMCs using the absorption lines and strong emission bands from Wolf–Rayet stars. The internal reddening is also estimated from the strength of the Na i D absorption lines. Based on these constraints, the observed spectra are matched with the synthetic spectra generated from a simple stellar population model. Several parameters of the clusters including age, reddening, cluster mass, and the underlying IMF are derived from the spectral matching. The ages of the YMCs range from 2.5 to 6.5 Myr, and these clusters contain stellar masses ranging from 1.6 × 10 ^5 M _☉ to 7.9 × 10 ^7 M _☉ . The underlying IMFs appear to differ from the universal form of the Salpeter/Kroupa IMF. Interestingly, massive clusters tend to have the bottom-heavy IMFs, although the masses of some clusters are overestimated due to the crowding effect. Based on this, our results suggest that the universal form of the IMF is not always valid when analyzing integrated light from unresolved stellar systems. However, further study with a larger sample size is required to reach a definite conclusion.